The Lasting Impact of Subsistence Style on Moral Norms and Attitudes: How the Way We Used to Eat Shapes Our Morality Today - Ma, Keunyoung (2018)
In the last few decades, the field of cultural psychology has received increasing attention due to the recognition that individual actions and thoughts are guided by more than one’s biology. Layering in the cultural context in which people exist has enriched our understanding of the human psyche but has also raised questions about the origins of cultural differences. This thesis explores one possible explanation, namely the historical subsistence style of a region. In the most basic sense, subsistence style refers to the way we used to eat, whether it be farming, herding, or hunting, and some cultural psychologists have found evidence suggesting that subsistence styles – even if they are no longer practiced – continue to shape contemporary cultures and their conceptions of morality. This thesis evaluates the theoretical underpinnings of Subsistence Style Theory and extrapolates its implications to moral attitudes and norms, including human rights, upheld by various cultures